Aatmanirbhar : a swadeshi paradigm - Mahajan, Ashwani (New Delhi : Rupa, 2023)
"This brilliant compendium of 18 essays penned by thought leaders from critically important fields is a road map to an aatmanirbhar Bharat. India$1 (Bs rudderless globalization for over three decades created an influx of companies, who generated wealth for their own countries, while adding to India$1 (Bs dependency on supplies from overseas. The pandemic exposed the acuteness of the situation and accentuated the weaponization of instruments of globalization, especially the international payment system and the supply of essential materials. This increase in domination by global powers forced many nations to lose faith in the idea of globalization. At this crucial juncture, came Prime Minister (PM) Narendra Modi$1 (Bs clarion call$1 (Bthe AatmaNirbhar Bharat Abhiyan. From the Nehruvian era, where government controlled all important industrial activity, the licence raj era, where government decided who could do business and how much, to the Modi era, where all coercive controls have been dismantled to create true economic freedom, India is finally knocking at the doors of economic greatness. This new vision for aatmanirbharta is radically different from Nehru$1 (Bs and focusses on best practices to produce for the world, while developing domestic capabilities to minimize dependence on imports, through a mix of innovative measures such as production-linked incentive schemes; technology support by the government; an actionable framework to rebuild industries battered by low-priced foreign goods; and promoting self-employment in rural areas. With a foreword from RSS Chief Mohan Bhagwat, this hugely significant book brings together a galaxy of experts from diverse domains, with the common intention of propelling India$1 (Bs resurgence"--s
Keywords: Aatmanirbhar Bharat (Program); Self-reliance--India.; India--Economic policy--2016-